The Role of Parents in Overcoming Online Game Addiction in Children - Yeni, Dini Putri; Parta, Muhammad Hakim; Busral, Busral; Kapitri, Neneng (Al-Ashri: Ilmu-Ilmu Keislaman, 2025)
This study aims to reveal the role of parents in overcoming online game addiction in school-age children, particularly in managing children's study time by controlling the duration of game play. Using a qualitative approach and descriptive methods, data were collected through observation, interviews, and documentation from parents and students. The results of the study show that parents can reduce online game addiction by making clear agreements about playing time, providing guidance on the dangers of game addiction, and implementing an open and understanding communication approach. Data analysis was carried out in four stages: collection, reduction, presentation, and conclusion. The implications of this study emphasize the importance of emotional involvement and effective communication between parents and children in shaping healthy digital habits, as well as encouraging the development of digital parenting education programs that emphasize mutual agreements and strengthening family relationships.